Symposium 6: Roles and Competencies of the e-Tutor - Denis, Brigitte; Watland, Philip; Pirotte, Sébastien; Verday, Nathalie (Proceedings of the International Conference on Networked Learning, 2004)
This paper considers the roles and competencies of the e-tutor. A literature review shows that different roles are assigned to the online tutors. Definitions of these roles are presented and discussed. Afterwards, we present eleven roles we consider important to manage the interactions between learners and tutors in an e-learning environment and the competencies needed to support these tutor’s roles. We conclude that to improve the quality of e-learning the tutor’s interventions have to be adapted to a specific context and we propose to train the e-tutors for these roles.